Adipose-Derived Cells (Stromal Vascular Fraction) Transplanted for Orthopedical or Neurological Purposes: Are They Safe Enough? - Katarzyna Siennicka; Aleksandra Zolocinska; Karolina Stepien; Natalia Lubina-Dabrowska; Marzena Maciagowska; Ewa Zolocinska; Anna Slysz; Renata Piusinska-Macoch; Slawomir Mazur; Urszula Zdanowicz; Robert Smigielski; Adam Stepien; et al. (Stem Cells International)
Although mesenchymal stem cells are used in numerous clinical trials, the safety of their application is still a matter of concern. We have analysed the clinical results of the autologous adipose-derived stem cell treatment (stromal vascular fraction (SVF) containing adipose-derived stem cells, endothelial progenitors, and blood mononuclear cells) for orthopedic (cartilage, bone, tendon, or combined joint injuries) and neurologic (multiple sclerosis) diseases. Methods of adipose tissue collection, cell isolation and purification, and resulting cell numbers, viability, and morphology were considered, and patient’s age, sex, disease type, and method of cell administration (cell numbers per single application, treatment numbers and frequency, and methods of cell implantation) were analysed and searched for the unwanted clinical effects. Results of cellular therapy were compared retrospectively to those obtained with conventional medication without SVF application. SVF transplantation was always the accessory treatment of patients receiving “standard routine” therapies of their diseases. Clinical experiments were approved by the Bioethical Medical Committees supervising the centers where patients were hospitalised. The conclusion of the study is that none of the treated patients developed any serious adverse event, and autologous mesenchymal stem (stromal) cell clinical application is a safe procedure resulting in some beneficial clinical effects (not analysed in this study).